HUBUNGAN ANTARA INOVASI PRODUK DAN KUALITAS PELAYANAN TERHADAP KEPUASAN KONSUMEN UMKM OLEH-OLEH KHAS DI KOTA PANGKALPINANG - Ary Fakturrachman Aryansyah; M. Afdal Samsuddin (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This study aims to analyze the effect of product innovation and service quality on customer satisfaction of souvenir-based MSMEs in Pangkalpinang City. A quantitative research approach was employed, utilizing primary data obtained from 120 consumer respondents through questionnaires and secondary data from relevant literature. Data analysis was conducted using Structural Equation Modeling-Partial Least Squares (SEM-PLS). The findings reveal that both product innovation and service quality have a positive and significant impact on customer satisfaction. Product innovation shows a stronger influence with a coefficient of β = 0.459 compared to service quality with β = 0.411. The coefficient of determination (R²) of 0.552 indicates that these two variables jointly explain 55.2% of the variation in customer satisfaction. These results highlight the crucial role of product innovation as a primary strategy for MSMEs to enhance customer satisfaction, which should be complemented by continuous improvements in service quality to strengthen competitiveness and maintain customer loyalty in the long term.